Mäṣḥafä fǝlsätu lä-abunä Täklä Haymanot: a Short Study - Nosnitsin, Denis (Aethiopica, 2003)
The account of the translation of the relics of abunä Täklä Haymanot, usually attached to his Acts, is one of the less-studied elements of the Saint’s hagiographic tradition. The article starts with a typology of translation reports in Ethiopian literature and deals in detail with the analysis of the textual tradition of the so-called Mäṣḥafä fǝlsätu lä-abunä Täklä Haymanot (‘Book of [the History] of the Translation [of the Body] of our father Täklä Haymanot’, BHT) and the problem of its sources. At least two stages can be distinguished in the development of the text (BHT1, BHT2), a long period of about two centuries separating them. The narrative of the first translation of the body of the Saint, which is said to have taken place in 1370, only becomes central in the later version of the work (BHT2). Among the literary relations around the BHT revealed in this study, the connection with the so-called Death of Moses, mostly known as a text affiliated to the literary tradition of the Betä Ǝsraʾel, is the most interesting one.